Citrus Mechanical Harvesting Systems--Continuous Canopy Shakers - Fritz M. Roka; Reza J. Ehsani; Stephen H. Futch; Barbara R. Hyman (EDIS)
Mechanization has been the hallmark of American agriculture. Nearly 100 percent of the agronomic crops grown in the United States are plowed, planted, and harvested with mechanical equipment. Mechanical harvesting equipment for sweet oranges has been studied extensively since the 1970s and during the 2005/06 harvest season, trunk and canopy shakers harvested more than 36,000 acres of Florida citrus. Mechanically harvested citrus acreage, however, has decreased significantly since 2005. During the 2012/13 season, less than 9,000 acres were mechanically harvested (FDOC 2013). Nevertheless, development and adoption of mechanical harvesting technology is important to the long-term economic sustainability of the Florida orange juice processing industry. This 5-page fact sheet describing canopy shakers. Written by F.M. Roka, R.J. Ehsani, S.H. Futch, and B.R. Hyman, and published by the UF Department of Food and Resource Economics, August 2014.